Estimation of Glycogen Content of Nematodes from Ovis Bharal, Aurangabad Region (M.S.), India - Baba Jadhav, Tushar Dhondge, Sujeet Jamdar* and (Journal of Experimental Sciences, 2010)
<div style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 1pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt"><p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 0in; MARGIN: 6pt 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-border-bottom-alt: solid windowtext .5pt; mso-padding-alt: 0in 0in 1.0pt 0in">In the present work, focus has been given to understand the mode of carbohydrate metabolism in parasites. The study of glycogen levels furnish the basic information about substrates and their intermediatory metabolites by which it is possible to get fair idea of metabolic pathway in which energy is derived by the nematode parasites. <p class="MsoNormal" style="BORDER-RIGHT: medium none; PADDING-RIGHT: 0in; BORDER-TOP: medium none; PADDING-LEFT: 0in; BACKGROUND: white; PADDING-BOTTOM: 0in; MARGIN: 6pt 0in 0pt; BORDER-LEFT: medium none; PADDING-TOP: 0in; BORDER-BOTTOM: medium none; TEXT-ALIGN: justify; mso-border-bottom-alt: solid windowtext .5pt; mso-padding-alt: 0in 0in 1.0pt 0in"> Department of Zoology, Dr.B.A.M.University Aurangabad (M.S.) India * Corresponding Author, Email: Â sujeetjamdar@gmail.com Please Cite This Article As: Tushar Dhondge, Sujeet Jamdar and Baba Jadhav. 2010. Estimation of Glycogen Content of Nematodes from Ovis Bharal, Aurangabad Region (M.S.), India. J. Exp. Sci. 1(2): 18-19.